Stability analysis for yield and component characters in ricebean (Vigna umbellata) - DOBHAL, V K; GAUTAM, N K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1988-91 to study the stability parameters for yield and 3 component characters in 11 genotypes of ricebean [Vigna umbellata (Thunb.) Ohwi & Ohashi]. Genotype X environment (G X E) interaction was significant for pods/plant, clusters/plant, pod length and yield/plant. Both linear and non-linear components were predominant in G X E interaction for all the characters, exceptfor clusters/plant where linear component accounted for most of the G X E interactions. GenotyPes 'RB 49' (19.89 g/plant) and 'RB 40' (20.40 g/plant) were high yielding and most stable for all the characters and could be utilized in a breeding programme. No significant correlation was observed among the 3 stability parameters (mean, bi and S2di) for all the characters. These parameters may therefore be considered whilebreeding stable varieties of ricebean.